The laws of Indo-European - Collinge, N. E. (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 1985)
This book collects all the named laws of Indo-European, presents each in its original form and rationale and then provides an evaluation of all major attacks, revisions and exploitations, along with a full bibliography and index. Complete - thorough - exhaustive.